PARTNERSHIP-DUAL TRAINING SYSTEM MODEL FOR BASIC SAFETY TRAINING TO IMPROVE VOCATIONAL EDUCATION TEACHER COMPETENCE - Kisno; Saut Purba; Arif Rahman; Sherly; Selviana Napitupulu (RADJA PUBLIKA, 2025)
Abstract